In Silico Primer Design and Genetic Analysis of Dipylidium caninum from Malang, Indonesia - Reza Yesica; Shelly Kusumarini R; Siti Muchibbatul Azizah (Journal of Applied Veterinary Science And Technology, 2026)
Background: Infection with Dipylidium caninum, a zoonotic cestode, is frequently observed in cats and may lead to significant gastrointestinal disturbances. For the detection of such parasites, Polymerase Chain Reaction (PCR) is widely employed due to its superior sensitivity and specificity. In the optimization of PCR performance, the design and in silico evaluation of primers are considered critical steps prior to experimental validation. Purpose:  Design and evaluation of PCR primers targeting mitochondrial COX1 and ND5 genes were undertaken to facilitate the detection of Dipylidium caninum, in cats from Malang, Indonesia. Method: Identification of COX1 and ND5 primers for Dipylidium caninum, was achieved through an in silico approach, with assessments based on nucleotide length, melting temperature (Tm), and GC content. Subsequent sequence analysis and primer evaluation were conducted using MEGA 11 software. Results: Generation of four primer pairs was accomplished, consisting of two pairs targeting the COX1 gene and two pairs targeting the ND5 gene. Adherence to recommended design criteria was observed in all primers, characterized by lengths of 18–30 nucleotides, melting temperatures of 50–65°C, and GC contents within the 40–60% range. DNA amplification was suggested by electrophoretic analysis. The highest evaluation score was attributed to the ND5A primer pair. Furthermore, clear clade separation between COX1 and ND5 gene sequences of Dipylidium caninum, was revealed through phylogenetic analysis. Conclusion: Potential for the detection of Dipylidium caninum, is demonstrated by the designed primers based on in silico evaluation; however, further laboratory validation via PCR assays and expanded sample sets remains necessary to confirm specificity, amplification efficiency, and broader diagnostic applicability.